1996
DOI: 10.1063/1.871986
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of detached and radiative divertor operation in Alcator C-Mod

Abstract: The divertor of the Alcator C-Mod tokamak routinely radiates a large fraction of the power entering the scrape-off layer. This dissipative divertor operation occurs whether the divertor is detached or not, and large volumetric radiative emissivities, up to 60 MW-m-3 in ICRF-heated discharges, have been measured using bolometer arrays. An analysis of both ohmic and ICRF-heated discharges has demonstrated some of the relative merits of detached divertor operation versus high-recycling divertor operation.An advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…What is least understood about the PFZ is why there is much plasma there at all given the short connection lengths from x-point to divertor plate and typical diffusive transport. Using spectroscopic measurements, it was observed that there is a significant recombination rate in the PFZ 17 ; Up to 10 22 recombinations/s occur there as compared to the plate ion current which can reach ~ 5x10 22 /s for these plasma currents (see Section IX). A drift across the outer divertor leg (between x-point and divertor plate) was postulated as the mechanism to supply the corresponding ion current to the PFZ.…”
Section: Effect Of Drifts On the Divertor Plasmamentioning
confidence: 99%
See 2 more Smart Citations
“…What is least understood about the PFZ is why there is much plasma there at all given the short connection lengths from x-point to divertor plate and typical diffusive transport. Using spectroscopic measurements, it was observed that there is a significant recombination rate in the PFZ 17 ; Up to 10 22 recombinations/s occur there as compared to the plate ion current which can reach ~ 5x10 22 /s for these plasma currents (see Section IX). A drift across the outer divertor leg (between x-point and divertor plate) was postulated as the mechanism to supply the corresponding ion current to the PFZ.…”
Section: Effect Of Drifts On the Divertor Plasmamentioning
confidence: 99%
“…For these studies, the X point had been shifted to larger major radius and up vertically to be in the field of view of the XUV spectrograph. These studies 22 show that the total radiation emissivity is dominated by XUV radiation. For plasmas with low central density (sheath-limited, n e ~ 1x10 20 m -3…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bolometry is used to monitor plasma radiation [30,31,32] and spectroscopic measurements are utilized to monitor specific impurity species, for example Mo and Cu. [33] The Mo and Cu densities are inferred using the measured line brightnesses, Thomson scattering electron density and temperature profiles, the MIST impurity transport code [34], transport coefficients [35] and cooling curves [36,37,38].…”
Section: Experimental Descriptionmentioning
confidence: 99%
“…In particular, the challenge posed by the heat flux impact on the vessel target inner surfaces has been considerably averted by means of divertor dissipative techniques [4]. In an MHD ideal tokamak the plasma is confined to a region of nested toroidal magnetic surfaces limited by one separatrix surface from the outer surfaces that divert the plasma exhaust to the target.…”
Section: Introductionmentioning
confidence: 99%